Case reportHypertrophic scars in a patient with Turner’s syndrome treated with recombinant growth hormone - Kędzia, Andrzej; Pawlaczyk, Mariola; Petriczko, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Turner’s syndrome is a common genetic disorder of girls and women, for which characteristic clinical symptoms encompass short stature, gonadal dysgenesis, systemic defects, multiple dysmorphic features and skin changes, including an increased number of melanocytic nevi, hypertrophic scars and keloids. The affected girls are treated with recombinant human growth hormone to improve the height. We present a case of a 15-year-old girl with Turner’s syndrome, hypertrophic scars and a keloid. At the age of 12 years and 8 months, the girl started recombinant human growth hormone treatment. During the therapy, a surgical excision of 4 out of 42 benign melanocytic nevi was performed. After 2 months the hypertrophic scars as well as a keloid were noted at sites of excision. Parents of girls with Turner’s syndrome undertake various attempts to improve not only the height and maturity of their daughters, but also their appearance by commonly performed surgical corrections of the webbed neck and pigmented nevi. The presented case suggests an increased risk of scars hypertrophy and keloid formations after surgical intervention in Turner’s syndrome patients who are treated with recombinant human growth hormone at the same time. Due to that it should be advised to postpone all planned surgical procedures until the therapy has been completed.